Freedom Comes from the Gift of Truth - Grygiel, Stanisław (Paedagogia Christiana, 2023)
The recently published Meditation on Giveness by John Paul II introduces us to the truth of a person through the mystery of love. Its light originates in God’s act of ‘creating man as man and woman’ as a gift of self for one another. One cannot understand humanity without contemplating man in the light of this act (the Beginning), ‘the universe and history’ referred to by John Paul II (Redemptor hominis [RH], 1979, No. 1), and opening oneself to the gift of truth. The latter comes to every person through the person to whom it is sent. According to John Paul II, the foundation for the understanding of all personal communions, including the Holy Trinity of Divine Persons, lies in the communion of man and woman in ‘one body.’ Adequate anthropology and theology of the body were developed around the idea of giveness as the foundation of marriage. The negation of the Beginning, or the Act of Creation, by modernity has blocked people’s path to the gift of truth, condemning them to the tragedy of absolute freedom that destroys human identity and introduces chaos into marriage, family, and nation, and through them also the Church and society. The Church and society shall be reborn not through a reform of the institutions they use to express themselves but through people who return to the Beginning. They are summoned by the personal beauty of man and the ‘image and likeness’ of the Beauty of the Divine Persons. It is through this personal Beauty that the Truth and the Path to Life, to which man is directed at the Beginning, are revealed. By denying the Act of Creation, modernity separates man away from the Truth and sends him toward pathless tracts where only death awaits him